A Cross-Sectional Survey of Socio-Demographic and Occupational Predictors of Work-Related Musculoskeletal Disorders among Artisanal Welders in North-Eastern Nigeria - Suleiman Mohammed; Mannir Kassim; Hamza Sabo Muhammad; Bishir Sabo; Usman Gidado (African Journal of Clinical Medicine and Pharmacy Research, 2026)
Artisanal welding involves high-intensity mechanical stress and sustained awkward postures, yet predictors of musculoskeletal morbidity in post-conflict economies remain insufficiently defined. This study evaluates the influence of socio-demographic and occupational predictors of work-related musculoskeletal disorders among artisanal welders in Maiduguri, North-Eastern Nigeria. A cross-sectional design was employed, involving 306 welders who completed a validated Standardized Nordic Questionnaire. Data were analyzed using descriptive statistics and Pearson’s chi-square tests to examine the relationships between demographic predictors, including age, professional experience, educational attainment, and the presence of work-related musculoskeletal disorders. The study cohort consisted predominantly of young workers, with a mean age of 26.84 ± 8.29 years, and a high proportion of respondents with secondary-level education. Despite this profile, musculoskeletal morbidity was widespread and intensified by limited recovery opportunities within the work environment. Inferential analysis showed that age, p = .085, professional experience, p = .296, and educational attainment, p = .831, were not significant predictors of work-related musculoskeletal disorders. These findings suggest an equalizing hazard effect, in which structural workplace deficits, particularly floor-level work and static loading, override individual biological, experiential, and educational differences. The study concludes that artisanal welders in structurally deficient work environments face non-discriminatory ergonomic risks across demographic strata. It contributes to occupational health research by highlighting a knowledge–practice gap in which general literacy does not translate into ergonomic agency without adequate workplace infrastructure. The findings imply that individual-focused behavioural interventions are insufficient and should be complemented by universal environmental engineering, including height-adjustable workstations and the integration of applied biomechanics into vocational training curricula to reduce long-term professional disability.